The great dilemma: the problem with multi-tiered clauses in Peru - Yano Tsuha, Nicolás Daichi (2020)
Multi-tiered arbitration clauses encourage the parties to adopt agreements to resolve their disputes, allowing them to avoid litigation, the deterioration of their commercial relations and the costs of arbitration. The advantages they provide have established them as a common agreement in practice. In this paper, the authors analyze the effect of existing contradictory rulings on the binding nature of these agreements, given the opposite positions of the Peruvian Constitutional Court and the Superior Court of Justice. Taking into account the legal nature of arbitration recognized in Peru, the authors propose that when an arbitral tribunal is faced with a breach of these clauses, it should refer the parties to comply with the terms of their agreement, as soon as the first opportunity after hearing the parties.